Pressures for change : a case study of centre city redevelopment in Canterbury - Sieracki, Karen Angela (University of Kent at Canterbury, 1983)
This thesis is a study of the redevelopment of the city centre of Canterbury. The period covered starts in 1940, but the main focus is on the 1970s and two specific projects: the Marlowe and Rosemary Lane sites. The analysis focuses on the link between the organisation of space and social processes, and examines the impact of the community ( eg residents groups) and local government on the redevelopment process. In order to develop a conceptual framework to study city centre redevelopment a review of pluralist, elitist, neo-elitist and Marxist approaches to community power is carried out. This leads to the concept of the context of local political decision making and the identification of four types of conflict underlying city centre redevelopment: (a) conflict over different uses of land - between commercial, access and residential uses, (b) conflict between the levels of government, (c) conflict between the local authority and the community and (d) conflict between the economic and political roles of the local authority as landowner and town planner. The advantage of this approach is that it avoids a static structural analysis and focuses on the pressures for change. The four potential bases of conflict are seen as deriving from the contradictory forces underlying city centre redevelopment. The findings of the study are as follows. Canterbury City Council was subject to external constraints in the form of financial and town planning powers possessed by higher levels of government. This had the effect of partly removing town planning issues from the local political arena, and prevented Canterbury City Council from being in sole control of the provision of new commercial developments, new car parks, and new roads. The internal decision making process of the Council was centred in a clique consisting of Chairmen and Vice-Chairmen of Council committees and senior officers. It was in this group that policy was formulated and decisions made. To a large extent local councillors were not accountable to the electorate due to the overwhelming majority of Conservative Councillors. As a result Canterbury Council excluded the articulation of many interests and this contributed to the dramatic rise in pressure group formation in the early 1970s. The two major developments aroused differing levels of public opposition. The Marlowe shopping development was less controversial than the Rosemary Lane car park development for three major reasons. Firstly, the "management tactics" of the Council were more successful with regard to the Marlowe site in the containment of political opposition. Secondly, the cost of the Rosemary Lane development was to be borne by the Council whereas the cost of the Marlowe development was perceived as being borne by the developer (the hidden costs of the development such as infrastructure were not taken into account and they would be met by the Council). Finally, the Marlowe development was seen as not generating as severe negative externality effects as the Rosemary Lane development, eg congestion, pollution, noise, etc. Canterbury City Council's policy can be seen as assisting commercial development and counteracting its negative externalities (eg increased traffic congestion, increased building and land rents, and pressure on the medieval infrastructure). It did this by the promotion of the Marlowe site commercial development, by building the Rosemary Lane multi-storey car park at its own expense and by containing political opposition. In this way the overall effect of Canterbury Council's policy was to assist private profitability and socialize the costs of private development.